2011
DOI: 10.1002/jssc.201100721
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and selective recognition of a novel solid‐phase microextraction fiber combined with molecularly imprinted polymers for the extraction of parabens in soy sample

Abstract: A prepared molecularly imprinted polymer with ethyl p-hydroxybenzoate as template molecule was applied for the first time to a homemade solid-phase microextraction fiber. The molecularly imprinted polymer-coated solid-phase microextraction fiber was characterized by scanning electron microscopy and thermogravimetric analysis. Various parameters were investigated, including extraction temperature, extraction time, and desorption time. Under the optimum extraction conditions, the molecularly imprinted polymer-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Molecularly imprinted polymers (MIPs) are robust materials and own high affinity originating from the “memory” cavities in MIPs skeleton, which are formed during preparation process . Furthermore, MIPs especially with sphere shape in micrometer size, can be very proper and effective packing agents in SPE process .…”
Section: Introductionmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are robust materials and own high affinity originating from the “memory” cavities in MIPs skeleton, which are formed during preparation process . Furthermore, MIPs especially with sphere shape in micrometer size, can be very proper and effective packing agents in SPE process .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that in the 19 studies analysed in this review, 35% of the imprinted polymers were prepared with MAA, particularly for analysis of parabens [40]. However other monomers were successfully employed in the synthesis of MIPs selective to parabens, namely 4-VP [41] and acrylamide [42] (Fig.…”
Section: Functional Monomermentioning
confidence: 99%
“…Commonly, the extraction efficiency of novel SPME fibers is evaluated by extraction of different analytes, such as polycyclic aromatic hydrocarbons (PAHs), BTEX, pesticides, and alcohols, in different environments including food samples , aqueous solutions , and biological environments . PAHs constitute a group of contaminants, which are widespread in the environment and also in foods .…”
Section: Introductionmentioning
confidence: 99%